The Evolution Of The Ideas Of National Awakening In The Poetry Of Ishaq Khan Ibrat - Maxsudjonov Otabek (International Journal Of Literature And Languages, 2025)
This article analyzes the gradual development (evolution) of national awakening ideas in the creative work of Ishaq Khan Ibrat, a major representative of Uzbek enlightenment literature of the late 19th and early 20th centuries. The analysis is directly based on the collection of Ibrat’s poems that have come down to us. The article highlights Ibrat’s transition from social criticism to calls for enlightenment, and then to the promotion of modernization and “culture.”